Colloquial Japanese the complete course for beginners - Clarke, H.D.B; Motoko Hamamura (Colloquial series.)
Offers a step-by-step approach to written and spoken Japanese. This title includes: dialogues covering a range of social and business situations; exercises with answer key; grammar reference section; extensive vocabulary lists, including Japanese script and romanization; and, an index of kanji, giving on and kun readings